Restrictions on Price Advertising - Peters, Michael (Journal of Political Economy, 1984)
In this paper the effects of advertising restrictions in an industry producing an undifferentiated product are analyzed. When the product is undifferentiated, advertising conveys information about price. The standard intuition suggests that such prohibitions will raise buyer search costs, making demand less elastic. This raises price and profits in an industry. Advertising restrictions provide an indirect means of coordinating pricing strategies in this framework. Here we consider the cost side of the same argument. The efficiency of firms in an industry is allowed to vary and information about costs is private. In this environment efficient firms are hurt by advertising restrictions, since lower advertised prices constitute their most effective competitive weapon. We show that when the number of buyers and sellers is finite, there is a nonzero probability that advertising restrictions will reduce every firm's price. This occurs when all firms are more efficient than their competitors expect them to be. Further, when the number of buyers and sellers is infinite, it is possible that average price charged in an industry can fall after a ban on advertising.